Analysis of Renal Trauma in Adult Patients: A 6-Year Own Experiences of Trauma Center - Zabkowski, Tomasz; Skiba, Ryszard; Saracyn, Marek; Zielinski, Henryk (Urology Journal, 2015)
Purpose: Abdominal trauma itself accounts for approximately 3% of all trauma cases. Among cases of multiple organ trauma, abdominal trauma accounts for 8-10% of cases. The frequency of genitourinary tract trauma is 10%. The renal trauma is 1-5% of all trauma cases. The aim of this study was to determine treatment’s strategy according to analysis of renal trauma severity. Materials and Methods: Since 2008, the Military Institute of Medicine, followed by the Trauma Center, treated 1119 trauma patients, of which 52 were renal trauma cases. In most cases, renal trauma was concomitant with multiple organ trauma. Results: Of the 52 renal trauma cases, 35 (67%) were caused by transportation, 5 (10%) by falls, 8 (15%) by iatrogenic factors, 2 (4%) by batteries, and 2 by idiopathic factors. In our study cohort, 31 cases (60%) experienced renal trauma concomitant with multiple organ trauma. Renal trauma involved injury to both kidneys in 9 (20%) patients, and to only 1 kidney in 34 (80%) patients. Conclusion: The use of computed tomography scan in combination with strict observation of conservative treatment protocols and intravascular techniques results in effective treatment of renal trauma.